PROBLEMS IN SUPPLY CHAIN OF POMEGRANATE (Punica granatum) IN ARGHANDAB DISTRICT, KANDAHAR PROVINCE, AFGHANISTAN - SURGUL AZIMI (The Journal of Research, PJTSAU, 2023)
Pomegranate plant has been grown since ancient times for its delicious fruits and as an ornamental garden for its red, orange or occasionally, creamy yellow flowers. Pomegranate (Punica granatum L.) belongs to the Punicaceae family. It is also known as the Chinese Apple or Carthage or Apple with many seeds. About 12 per cent of the total land in Afghanistan is arable and less than 6 per cent currently is cultivated. Agriculture is the backbone of the Afghan economy; according to the statistical book FY (2017-18) the contribution agriculture to the country Gross Domestic Product (GDP) was 20.9 per cent while the labor force engaged in this sector is around 60.8 per cent. The annual growth rate of pomegranate production in Afghanistan was predicted at 2.9 per cent (Fitrat, 2014). Pomegranate contribute of the total population of Afghanistan was about (2) per cent to the total horticultural production in Afghanistan. The local varieties grown in the main production areas of Kandahar province are known for their high quality and productivity. Different varieties of pomegranates are produced in Afghanistan and supplied to the local markets. Through the maturity time of the crop varies according to the climatic conditions, usually the fruit comes into the market during summer and continues into the fall season. The Agriculture sector is entirely run by private enterprise, including farmers, cooperatives, inputs suppliers, herders, agribusiness processors, and exporters. Kandahar province is recognized worldwide for its high quality pomegranate production especially the Kandahar varieties, which are highly preferred by national and international consumers. Of the total land under pomegranate cultivation in the country, Kandahar share is about 36.7 per cent with 39.5 per cent of the total national production. But due to poor orchard management practices, careless production, widespread pest and diseases, lack of quality inputs and lack of technical and financial support to the farmers both quality and quantity of pomegranate is badly affected and gradually decreasing.